Efficacy and Safety of Remimazolam in Short Endoscopic Procedures: A Systematic Review and Meta-Analysis - Yueyang Xin; Pei Lu; Shaodi Guan; Shaomeng Si; Rao Sun; Wei Xia; Hui Xu (Medicina)
Background and Objectives: Appropriate sedation and anesthesia are crucial for ensuring comfortable endoscopic procedures. Propofol is one of the most often used sedatives. However, its safety and adverse effects restrict its usage. Remimazolam is a relatively new intravenous benzodiazepine that offers many benefits. Our analysis aims to evaluate the effectiveness and safety of remimazolam during short endoscopic procedures. Materials and Methods: We conducted a comprehensive search of the PubMed, Web of Science, ClinicalTrials.gov, and Turning Research Into Practice databases up to 31 December 2023, for randomized controlled trials published in English. Statistical analyses were performed using Cochrane Review Manager 5.4.1 and Stata Software/MP. Results: The success rate of sedation with remimazolam was slightly lower than that with propofol (RR: 0.99, 95% CI: 0.98~1.00; p = 0.004; I2 = 42%). As for anesthetic effect-related outcomes, remimazolam did not show advantages in onset time (MD = 12.72, 95% CI: 6.53~18.90, p < 0.001, I2 = 94%), recovery time (MD = 0.86, 95% CI: −0.55~2.27, p = 0.23, I2 = 98%), or intraoperative body movement (RR: 1.18, 95% CI: 0.60~2.32, p = 0.62, I2 = 87%). However, compared to propofol, remimazolam significantly reduced the incidence of several adverse events, including injection pain (RR: 0.07, 95% CI: 0.03~0.14, p < 0.001, I2 = 69%), intraoperative hypotension (RR: 0.38, 95% CI: 0.31~0.47, p < 0.001, I2 = 65%), bradycardia (RR: 0.25, 95% CI: 0.15~0.45, p < 0.001, I2 = 0%), and respiratory depression (RR: 0.34, 95% CI: 0.25~0.46, p < 0.001, I2 = 50%). The incidence of postoperative nausea and vomiting (PONV) was slightly higher with remimazolam (RD: 0.01, 95% CI: 0.00~0.03, p = 0.04, I2 = 33%). Conclusions: Remimazolam is a promising sedative for short endoscopic procedures due to its superior safety profile despite a slightly lower sedation success rate compared to propofol.